Polymersomes as Stable Nanocarriers for a Highly Immunogenic and Durable SARS-CoV‑2 Spike Protein Subunit Vaccine - Lam, Jian Hang; Khan, Amit K; Cornell, Thomas A; Chia, Teck Wan; Dress, Regine J; Yeow, Wen Wang William; Mohd-Ismail, Nur Khairiah; Venkataraman, Shrinivas; Ng, Kim Tien; Tan, Yee-Joo; Anderson, Danielle E; Ginhoux, Florent; et al. (ACS nano, 2021)
Multiple successful vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are urgently needed to address the ongoing coronavirus disease 2019 (Covid-19) pandemic. In the present work, we describe a subunit vaccine based on the SARS-CoV-2 spike protein coadministered with CpG adjuvant. To enhance the immunogenicity of our formulation, both antigen and adjuvant were encapsulated with our proprietary artificial cell membrane (ACM) polymersome technology. Structurally, ACM polymersomes are self-assembling nanoscale vesicles made up of an amphiphilic block copolymer comprising poly(butadiene)-b-poly(ethylene glycol) and a cationic lipid, 1,2-dioleoyl-3-trimethylammonium-propane. Functionally, ACM polymersomes serve as delivery vehicles that are efficiently taken up by dendritic cells (DC1 and DC2), which are key initiators of the adaptive immune response. Two doses of our formulation elicit robust neutralizing antibody titers in C57BL/6 mice that persist at least 40 days. Furthermore, we confirm the presence of functional memory CD4+ and CD8+ T cells that produce T helper type 1 cytokines. This study is an important step toward the development of an efficacious vaccine in humans.